1987
DOI: 10.1177/000841748705400306
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Graduate Education: The Scientist-Practitioner Model

Abstract: The development of a scientific based practice is essential if occupational therapists are to defend their practice against scepticism and budget cuts. In order to equip the profession with the skills necessary to develop a scientific basis for practice, it is generally considered that graduate programs in occupational therapy should be initiated. This paper argues that to be most effective a specific kind of graduate program is required -one based on the scientist-practitioner model. This model provides for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…These models have tended to concentrate on the way in which a ‘role’ can incorporate research activity. Colborn (1993) and Polatajko and MacKinnon (1987) for example, put forward the occupational therapy roles of scientist‐practitioner, and practitioner‐researcher as models which demonstrate the way in which clinicians can do research. These were based on models from practice professions such as nursing ( Lieske, 1986; Knafl et al , 1989 ; Wade, 1995), medicine ( Wise, 1996), social work ( Scott, 1990), and counselling psychology ( Hersen & Barlow, 1976; Gelso, 1979; Kiesler, 1981; Barlow et al , 1984 ; Magoon & Holland, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These models have tended to concentrate on the way in which a ‘role’ can incorporate research activity. Colborn (1993) and Polatajko and MacKinnon (1987) for example, put forward the occupational therapy roles of scientist‐practitioner, and practitioner‐researcher as models which demonstrate the way in which clinicians can do research. These were based on models from practice professions such as nursing ( Lieske, 1986; Knafl et al , 1989 ; Wade, 1995), medicine ( Wise, 1996), social work ( Scott, 1990), and counselling psychology ( Hersen & Barlow, 1976; Gelso, 1979; Kiesler, 1981; Barlow et al , 1984 ; Magoon & Holland, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They will bring to the profession a solid grounding in liberal arts or science. They will be able to embrace rapidly the tradition of the scientist-practitioner (Polatajko and MacKinnon 1987). It will be interesting and important to follow the trajectories of these graduates beyond lift-off!…”
Section: Resultsmentioning
confidence: 99%
“…The occupational therapy profession has begun to recognise the importance of evidence-based practice (Ottenbacher 1987, Polatajko and MacKinnon 1987, Strong 1999. In qualitative research regarding therapists' perceptions of evidence-based practice, Dubouloz et al (1999) found that therapists believed themselves to be disadvantaged by lack of research expertise.…”
Section: Imperatives International Imperatives For Increased Educatiomentioning
confidence: 99%
See 1 more Smart Citation
“…W ithin the occupational therapy literature, discussions related to the need for research in our field (Barris & Kielhofner, 1985;Baum, Boyle, & Edwards, 1984;Grady, 1987;Polatajko & MacKinnon, 1987) and investigations of clinicians' attitudes toward research and research activities (Colborn, 1993;Cusick, Franklin, & Rotem, 1999;Cusick & Rotem, 1994) are clearly evident. However, a review of the literature revealed few current descriptions (Bloomer, 1995;Clark, 1986) of how occupational therapy educators actually translate their beliefs about the fundamental importance of research into educational practice.…”
mentioning
confidence: 99%